2017
DOI: 10.1074/jbc.m117.800904
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modification of the membrane type 1 matrix metalloproteinase (MT1-MMP) cytoplasmic tail impacts ovarian cancer multicellular aggregate dynamics

Abstract: Membrane type 1 matrix metalloproteinase (MT1-MMP, MMP-14) is a transmembrane collagenase highly expressed in metastatic ovarian cancer and correlates with poor survival. Accumulating evidence shows that the cytoplasmic tail of MT1-MMP is subjected to phosphorylation, and this post-translational modification regulates enzymatic activity at the cell surface. To investigate the potential role of MT1-MMP cytoplasmic residue Thr phosphorylation in regulation of metastasis-associated behaviors, ovarian cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Dynactin also participates in vesicular trafficking of matrix metalloproteinase-14 (MT1-MMP or MMP-14) 40 . Given the involvement of MMP-14 in HER2+ cancer cell invasion 41 43 , it will be interesting to test for the effects of Myc B on Dynactin and MMP-14 activity in these models in future studies aimed at understanding comprehensive effects of actin disruption in metastatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Dynactin also participates in vesicular trafficking of matrix metalloproteinase-14 (MT1-MMP or MMP-14) 40 . Given the involvement of MMP-14 in HER2+ cancer cell invasion 41 43 , it will be interesting to test for the effects of Myc B on Dynactin and MMP-14 activity in these models in future studies aimed at understanding comprehensive effects of actin disruption in metastatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Moss et al showed that phospho-mimetic Thr 567 mutants exhibit higher collagenolytic activity and three-dimensional growth within a collagen matrix, thereby promoting enhanced matrix invasion in ovarian cancer cells [88]. In addition, phosphorylation of Thr 567 impacted the integrity of cell monolayer, cell motility and multicellular aggregate dynamics in ovarian cancer cells, promoting metastasis-associated behaviors [89]. Furthermore, a study by Nyalendo et al reported that phosphorylation at Tyr 573 influenced cell migration, suggested by the ability of a phospho-defective mutant to inhibit migration of cells endogenously expressing MMP14 [90].…”
Section: Ptms—an Additional Level Of Protein Regulationmentioning
confidence: 99%
“…MMP-9 is expressed by primary ovarian carcinoma cells derived from the ovary, metastatic implants and ascites [ 194 ]. A recent study has revealed that MT1-MMP is one of the MMPs that contribute to the detachment of multicellular aggregates floating in the ascites microenvironment [ 195 ]. MMP-2 is also found to be abundantly expressed by the multicellular aggregates derived from ascites and is thought to play a major role in early metastasis by facilitating the rapid disaggregation of the ovarian cancer cells for adhesion to the mesothelial surface [ 196 ].…”
Section: Metzincins and Timps In Ovarian Cancermentioning
confidence: 99%